2015
DOI: 10.5489/cuaj.2927
|View full text |Cite
|
Sign up to set email alerts
|

Is there a gender effect in bladder cancer? A population-based study of practice and outcomes

Abstract: Introduction: The incidence of bladder cancer varies by gender. Whether differences exist between women and men in extent of disease, treatment, and outcome is not well-described. We evaluate gender differences in bladder cancer using a population-based cohort. Methods: Electronic records of treatment were linked to the population-based Ontario Cancer Registry to identify all patients with bladder cancer treated with cystectomy or radical radiotherapy (RT) in Ontario between 1994 and 2008. We compare extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
2
10
2
2
Order By: Relevance
“…A somewhat greater age difference between males and females (1 year [3] vs. 3.1 years in this study) and a less favorable stage distribution in females are further demographic differences between the current and the cited study [3]. A similar difference between females and males concerning the presence of extravesical disease (T3-4, 58.7 vs. 47.2% [8]) as in the current study was observed in a recent multicenter study from Austria [7], whereas in a Canadian multicenter study that observed narrowly identical mortality rates lower differences (T3-4 in females 61 vs. 58% in males [6]) were found. In one multicenter study, a lower 90-day mortality rate was observed in females [9], a finding that was not confirmed in our study (Table 1).…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…A somewhat greater age difference between males and females (1 year [3] vs. 3.1 years in this study) and a less favorable stage distribution in females are further demographic differences between the current and the cited study [3]. A similar difference between females and males concerning the presence of extravesical disease (T3-4, 58.7 vs. 47.2% [8]) as in the current study was observed in a recent multicenter study from Austria [7], whereas in a Canadian multicenter study that observed narrowly identical mortality rates lower differences (T3-4 in females 61 vs. 58% in males [6]) were found. In one multicenter study, a lower 90-day mortality rate was observed in females [9], a finding that was not confirmed in our study (Table 1).…”
Section: Discussioncontrasting
confidence: 41%
“…The 21.8% rate of administration of adjuvant cisplatinbased chemotherapy in the current study was narrowly identical with the rates observed in multicenter studies [3,6]. This rate contrasts with 48.9% high risk patients with either extravesical or lymph node-positive disease who could be candidates for such treatment (Table 1).…”
Section: Gender and Mortality After Radical Cystectomycontrasting
confidence: 47%
See 2 more Smart Citations
“…The finding that TEA use was less frequent in women is of interest and potentially highlights perceived inequities in management and outcomes of women with bladder cancer. 28 Despite its recognized importance in early outcomes in related surgical populations, 8,9 there is a paucity of evidence supporting TEA-associated improvement of patient outcomes in RC. Evidence often quoted supporting use of TEA in reduction of short-term complications in RC come from the ERAS literature.…”
Section: Discussionmentioning
confidence: 99%